Investing in developing countries — Chances, hazards, facts - Dietmar Petersen (Intereconomics, 1978)
From its beginnings on the DEG (German Development Company) has always been working with two aims in mind. Development policy provided one and the external economic relations of the Federal Republic of Germany the other. It is contributing to economic development by supporting investments by German firms in the Third World and by encouraging cooperation between German investors and local businessmen on a partnership basis.
Keywords: 330; Direct Investment